2022
DOI: 10.1021/acs.estlett.2c00016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Brown Carbon on the Tibetan Plateau: Regional Differences in Chemical Composition and Light Absorption Properties

Abstract: Fine particulate matter (PM 2.5 ) filter samples were collected from two high-altitude remote sites located in the southern (QOMS) and northern (WLG) regions of the Tibetan Plateau (TP) to explore the regional differences in brown carbon (BrC) properties. Chemical differences in BrC composition representative of these two areas were inferred from molecularlevel analysis of the PM 2.5 samples using high-performance liquid chromatography coupled with photodiode array and highresolution mass spectrometry detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Meanwhile, the ambient BrC samples over the regions of Erenhot, northern China (Wen et al, 2021), Patiala (Srinivas et al, 2016) and New Delhi, India (Kirillova et al, 2014) lie in the mixed regions of moderately and weakly absorbing BrC, which also confirmed the dung combustion influences. These comparisons further verified that the BrC emitted from dung combustion over TPL regions exhibited strong absorption abilities, which can be mainly attributed to the low-temperature and smoldering combustion conditions (Xu et al, 2022;Zhou et al, 2021;Saleh, 2020). In comparison, the ambient BrC samples in the region of Rondonia, Brazil with active biomass burning influences and near-source BrC samples emitted from biomass burning and coal combustion with sufficient oxygen supply, mainly fall into the region of weakly absorbing BrC (Park et al, 2020;Zhao et al, 2022;Ni et al, 2021;Zhang et al, 2022b).…”
Section: Overview Of Light Absorption Of Brcsupporting
confidence: 56%
See 1 more Smart Citation
“…Meanwhile, the ambient BrC samples over the regions of Erenhot, northern China (Wen et al, 2021), Patiala (Srinivas et al, 2016) and New Delhi, India (Kirillova et al, 2014) lie in the mixed regions of moderately and weakly absorbing BrC, which also confirmed the dung combustion influences. These comparisons further verified that the BrC emitted from dung combustion over TPL regions exhibited strong absorption abilities, which can be mainly attributed to the low-temperature and smoldering combustion conditions (Xu et al, 2022;Zhou et al, 2021;Saleh, 2020). In comparison, the ambient BrC samples in the region of Rondonia, Brazil with active biomass burning influences and near-source BrC samples emitted from biomass burning and coal combustion with sufficient oxygen supply, mainly fall into the region of weakly absorbing BrC (Park et al, 2020;Zhao et al, 2022;Ni et al, 2021;Zhang et al, 2022b).…”
Section: Overview Of Light Absorption Of Brcsupporting
confidence: 56%
“…In 2019, Zhang et al (2022a) confirmed that the consumption of animal dung includes yak and sheep was as high as 10,990 Gg during the heating season over TPL region, which can be treated as a major biomass resource. It's well-known that the burnings of household animal dung fuels, commonly lead to smoldering processes with low temperature and oxygen deficient conditions, are favor to produce an abundance of lightabsorbing brown carbon (BrC) (An et al, 2019;Xu et al, 2022;Zhang et al, 2022a). Atmospheric BrC, as a unique of organic compounds, absorbs light significantly across the entire ultraviolet−visible (UV−Vis) wavelengths, which also brings considerable changes in atmospheric oxidation processes, atmospheric pollution and radiative forcing over TPL region (Al-Abadleh et al, 2021;You et al, 2020;Zhang et al, 2017b;Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is literature evidence that PM extracts using acetonitrile for instance leads to a more absorbing fraction. 29 Here, we address experimental variability by reporting 1 O 2 quantum yields and by linking [ 1 O 2 ] ss to mass spectrometry data. The seasonality of the absorbance of the water-extracted fraction of the PM 10 filters is also consistent with the [ 1 O 2 ] ss seasonality peaking in the wintertime (Figure 2 middle).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Note that these [ 1 O 2 ] ss values represent lower limits since the filters were extracted with water and therefore only represent the water-soluble fraction of PM 10 and thus a subset of 1 O 2 sensitizers. There is literature evidence that PM extracts using acetonitrile for instance leads to a more absorbing fraction . Here, we address experimental variability by reporting 1 O 2 quantum yields and by linking [ 1 O 2 ] ss to mass spectrometry data.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the averaged Babs,BrC at 370 nm were 4.42, 0.69, and 0.60 Mm −1 at the three sites, respectively, which finally contributed 33.1%, 21.3%, and 22.4% of the total Babs, correspondingly. The significantly higher values of total Babs, Babs,BC, and Babs,BrC and the higher BrC contribution in the southern TP region might be related to the important contributions of light-absorbing carbonaceous aerosols from the transported biomass burning emissions (Xu et al, 2020(Xu et al, , 2022.…”
Section: Aerosol Optical Properties and Light Absorptions From Bc And...mentioning
confidence: 99%